A cocktail of MCM2 and TOP2A, p16INK4a and Ki-67 as biomarkers for the improved diagnosis of cervical intraepithelial lesion - Yang, Qi-chang; Zhu, Yan; Liou, Hong-bing; Zhang, Xiao-juan; Shen, Yi; Ji, Xiao-hua (Polish Journal of Pathology, 2013)
The purpose of this paper was to explore the immunohistochemistry (IHC) results for a cocktail of minichromosome maintenance protein 2 (MCM2) and topoisomerase II (TOP2A), p16 INK4a and Ki-67 as biomarkers for the diagnosis of cervical intraepithelial neoplasia (CIN), improving the routine interpretation of cervical histopathology. 133 cases of CIN were collected from the archival data. All routine hematoxylin and eosin (HE)-stained slides of the subjects were re-examined independently by three senior pathologists, to provide a “consensus diagnosis”. Immunohistochemistry for the three biomarkers was performed, and the results were reviewed independently of the corresponding archival diagnosis to make a “diagnosis assisted by IHC” by the original pathological practitioners. The diagnosis accordance rate of the archival original diagnosis with the “consensus diagnosis” and the “diagnosis assisted by IHC” with the “consensus diagnosis” were verified by Fisher’s exact test. The results showed that raw agreement between the original HE diagnosis and the “consensus diagnosis” was 88.55%, and raw agreement between the “diagnosis assisted by IHC” and the “consensus diagnosis” was 95.78%. The latter was significantly higher than the former (Fisher’s exact test, p = 0.023). In conclusion, the three biomarkers had a high degree of sensitivity and specificity, and appear to be a useful and reliable diagnostic adjunct to improve the routine diagnosis, and reduce inter-observer variability in cervical biopsy specimens.